Peran Koperasi Wanita “SUMBER JAYA” Dalam Meningkatkan Perekonomian Wanita - Rikha Irmawati; Ilmi Usrotin Choiriyah (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
The economic condition of society in general, especially women, is a very important factor in empowering society in the economic sector. Economic empowerment is carried out to reduce poverty rates and increase welfare to develop women to be more productive so that they can increase the level and standard of living of women and improve family welfare. "SUMBER JAYA" Women's Cooperative, which is one of the women's cooperatives that has succeeded in doing this and is committed to providing business capital assistance so that it can help the economy of the people who are members of the organization. The purpose of writing this research is to describe and analyze the role of the "SUMBER JAYA" Women's Cooperative in improving the economy, especially women. This research uses a qualitative descriptive research method. The results of the research show that the role of cooperatives in improving women is still not optimal, there is a lack of administrators which causes multiple positions and there are still many bad loans which hinder the circulation of money in cooperatives.